The Role of Extracellular Matrix in the Experimental Acute Aortic Regurgitation Model in Rats - Bussoni, Marjory [UNESP] (2022)
Background: Mechanisms involved in cardiac remodelling by aortic regurgitation (AR) and the moment when cardiac dysfunction begins are largely unknown. This study aimed to investigate cardiac morphology and function after 1, 4, 8, and 12 weeks of experimental AR in Wistar rats. Extracellular matrix was also investigated as the potential mechanism that underlies the AR remodelling process. Methods: Male Wistar rats underwent surgical acute AR (AR group, n=51) or a sham surgery (sham group, n=32). After the procedure, serial transthoracic echocardiograms were performed at 1, 4, 8, and 12 weeks. Morphometry of cardiac tissue and the activities of metalloproteinase 2 (MMP-2) and tissue metalloproteinase inhibitor-1 (TIMP-1) were analysed. Statistical analysis was performed by two-way ANOVA. Significance level was 5%. Results: The AR group presented an increase in the sphericity index (week 1); an increase in the left atrium, left ventricular mass index, TIMP-1 and MMP-2 activities, and collagen fraction (week 4); an increase in myocyte area (week 8); and a reduction in fraction shortening (week 12). First, the chamber became more spherical; second, MMP-2 and TIMP-1 were activated and this may have contributed to hypertrophy and atrial enlargement, until systolic dysfunction occurred. Conclusions: This study showed a sequence of abnormalities that preceded myocardial dysfunction in an experimental model of AR. First, haemodynamic volume overload led to a more spherical left ventricle chamber. Second, MMP-2 and TIMP-1 transitorily increased and may have contributed to atrial enlargement, eccentric hypertrophy, and systolic dysfunction.